Spinster with a scandalous past - King, Sadie (Harlequin Books, 2024)
Staying with her aunt for the summer, hoping to finally put the past behind her, spinster Louisa Conrad meets the baronet of Hayton Hall, Sir Isaac Liddell--a man so broodingly abrasive, she's determined to keep her distance! Until she discovers why he's that way, with experiences so like her own she can't help but fall for him. Yet Louisa cannot let him closer unless he knows the truth of her past...but telling him risks losing everything!